2017
DOI: 10.1038/srep39850
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genetic susceptibility loci for intestinal Behçet’s disease

Abstract: Several recent genome-wide association studies (GWAS) identified susceptibility loci/genes for Behçet’s disease (BD). However, no study has specifically investigated the genetic susceptibility loci associated with intestinal involvement in BD. We aimed to identify distinctive genetic susceptibility loci/genes associated with intestinal involvement in BD and determine their roles in intestinal inflammation as well as their interactions with genes involved in inflammatory bowel disease (IBD). GWAS and validation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 39 publications
1
14
0
2
Order By: Relevance
“…Four-µm-thick paraffin sections of the distal colon of each animal or of cells were stained with PAS stain or Alcian blue, respectively, according to standard procedures to evaluate the histopathology and goblet cells. Immunohistochemistry was performed using anti-mouse MTNR1A (1:500; Abcam, Cambridge, MA, USA), as previously described 58,63 . After incubation with anti-mouse Reg3β (1:200, R&D Systems, Minneapolis, MN, USA), sections were incubated with Alexa Fluor-488-conjugated secondary antibodies (Thermo Fisher Scientific, San Jose, CA, USA) for immunofluorescence stains.…”
Section: Methodsmentioning
confidence: 99%
“…Four-µm-thick paraffin sections of the distal colon of each animal or of cells were stained with PAS stain or Alcian blue, respectively, according to standard procedures to evaluate the histopathology and goblet cells. Immunohistochemistry was performed using anti-mouse MTNR1A (1:500; Abcam, Cambridge, MA, USA), as previously described 58,63 . After incubation with anti-mouse Reg3β (1:200, R&D Systems, Minneapolis, MN, USA), sections were incubated with Alexa Fluor-488-conjugated secondary antibodies (Thermo Fisher Scientific, San Jose, CA, USA) for immunofluorescence stains.…”
Section: Methodsmentioning
confidence: 99%
“…Similar to IBD, intestinal BD is known to have a wax-and-wane disease course and frequent relapse, even with surgery 5 ; however, data regarding disease pathogenesis are extremely limited. Because we recently reported that genetic variants in IL17A , IL23R , STAT4, NAALADL2 , and YIPF7 are associated with intestinal BD pathogenesis 12,13 , in this study, we aimed to investigate differentially expressed proteins of intestinal BD using a proteomics approach.…”
Section: Discussionmentioning
confidence: 99%
“…In general, intestinal BD has similar clinical and therapeutic characteristics to IBD. However, although we recently identified several genetic loci ( IL17A , IL23R , STAT4, NAALADL2 , and YIPF7 ) associated with susceptibility to intestinal BD 12,13 , relatively little is known about the disease pathogenesis of intestinal BD, highlighting the need for further study to aid in the diagnosis and treatment of this disease.…”
Section: Introductionmentioning
confidence: 99%
“…Показано, что в пределах гена находится точка разрыва для транслокации, ассоциированной с развитием синдрома Корнелии де Ланге -редкого синдрома нарушения развития [8]. Редкий аллель полиморфизма rs3914501 гена связан с развитием синдрома Корнелии де Ланге и болезни Кавасаки [9]. С болезнью Кавасаки также связан однонуклеотидный полиморфизм rs17531088 гена NAALADL2 [10].…”
Section: однонуклеотидныйunclassified
“…Интересно, что в состав фенотипических характеристик синдрома Корнелии де Ланге входят и пороки сердца (дефекты перегородок, стеноз легочной артерии, коарктация аорты) [11]. Тогда как синдром (болезнь) Кавасаки представляет собой системный васкулит новорожденных и детей [9]. Кроме того, однонуклеотидный полиморфизм rs3914501 гена NAALADL2 по данным GWAS ассоциирован с поражением кишечника при болезни Бехчета.…”
Section: однонуклеотидныйunclassified